Skin cancer: symptoms, mechanistic pathways and treatment rationale for therapeutic delivery. (May 2017) - Goyal, Neha; Thatai, Purva; Sapra, Bharti
Cancer is a group of diseases categorized by abandoning escalation and multiplication of abnormal cells. Current topical treatments for skin cancer are mainly in the semisolid dosage forms of 5-fluorouracil, imiquimod, etc. Many surgical treatments are also available these days for the treatment of skin cancer, for example, photodynamic therapy, which is approved by the US FDA. The stratum corneum is the main barrier against permeation of topical formulations developed for skin cancer treatment. Liposomes, thermosensitive stealth liposomes, nanoemulsions and polymeric lipid nanoparticles have been used by several researchers to increase skin permeability. In the present paper, major aspects of formulations developed for skin cancer, various types of skin cancer, its etiology and pathogenesis have been emphasized.